Biorefineries in circular bioeconomy: A comprehensive review - Ubando, Aristotle T. (Animo Repository, 2020)
Biorefinery is a sustainable means of generating multiple bioenergy products from various biomass feedstocks through the incorporation of relevant conversion technologies. With the increased attention of circular economy in the past half-decade with the emphasis of holistically addressing economic, environmental, and social aspects of the industrial-sector, biorefinery acts as a strategic mechanism for the realization of a circular bioeconomy. This study presents a comprehensive review of different biorefinery models used for various biomass feedstocks such as lignocelluloses, algae, and numerous waste-types. The review focuses on how biorefinery is instrumental in the transition of various biomass-based industries in a circular bioeconomy. The results reveal that the social-economic aspect of the industrial sector has a major influence on the full adoption of biorefineries in circular bioeconomy. Biomass wastes have played a major role in the implementation of biorefinery in circular bioeconomy. The current challenges are also presented along with future perspectives. © 2019 Elsevier Ltd